How Grief Camp Reinforces the Need for Death Education in Elementary Schools - Keri-Lyn Durant (Canadian Journal for New Scholars in Education, 2018)
Abstract: Established to help normalize the grieving process (Schuurman & Decristofaro, 2010), grief camps are traditionally for children and adolescents who have experienced a death-related loss. These camps take children and adolescents out of their daily environment, inviting them to express their grief in innovative and developmentally appropriate ways (Christ, 2000; Koocher, 1973; Laing & Moules, 2015; Neimeyer & Currier, 2009; O’Connor, 2002-2003; Schuurman & Decristofaro, 2010; Tonkins & Lambert, 1996). I am a volunteer at two grief camps in Manitoba and it is apparent that these camps not only fill a gap in the bereavement experiences of children and adolescents, but also highlight the need for more preparation in terms of dying, death, and loss. Pupils in Ontario spend almost 6,000 hours in elementary school (OECD, 2014), yet there is no curriculum that directly addresses death. As a microcosm, grief camp reinforces the need for death education on a macro level in elementary schools.